Cross-Disciplinary Perspectives on Regional and Global Security (Springer International Publishing, 2018)
This book focuses on current key issues of international security from an actor-centered approach. The volume is divided into 3 sections: the first part analyses an array of security issues in Europe, the second one explores how those security issues play out in Americas and the third focuses on Africa. Each of the chapter authors outlines the relevant ideas, interests and institutions. The volume provides an overview of how global, regional, and national actors, differ in their management approaches, capacity levels, and how these differences translate into cross-regional cooperation on security issues. Paweł Frankowski is Assistant Professor in the Institute of Political Science and International Relations at the Jagiellonian University Artur Gruszczak is Associate Professor in the Institute of Political Science and International Relations at the Jagiellonian University.